PARATYPIC VARIABILITY OF THE PERIOD BETWEEN SHOOTING AND EARING STAGES OF DAGESTANIAN BARLEYS - I. A. Zveinek; R. A. Abdullaev; B. A. Batasheva; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
For three years 265 barley accessions from Dagestan were analyzed for the duration of the period between shooting and earing stages. Under the conditions of south planar area of Dagestan, the early accessions k-15008 and k-15013 have been selected. The accession k-15027 was characterized by a high rate of development in the Northwestern area of the country. The Dagestanian barleys were found to be strongly affected by the growing conditions, notably they have a high norm of reaction. It is concluded that vernalization temperatures, short day and high temperatures during the vegetation period promote earliness of barley.